Designing of Medium-Size Humanoid Robot with Face Recognition Features - Christian Tarunajaya; Oey, Kevin Wijaya; Reinard Lazuardi Kuwandy; Heri Ngarianto; Alexander Agung Gunawan; Widodo Budiharto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2015)
Nowadays, there have been so many development of robot that can receive command and do speech recognition and face recognition. In this research, we develop a humanoid robot system with a controller that based on Raspberry Pi 2. The methods we used are based on Audio recognition and detection, and also face recognition using PCA (Principal Component Analysis) with OpenCV and Python. PCA is one of the algorithms to do face detection by doing reduction to the number of dimension of the image possessed. The result of this reduction process is then known as eigenface to do face recognition process. In this research, we still find a false recognition. It can be caused by many things, like database condition, maybe the images are too dark or less varied, blur test image, etc. The accuracy from 3 tests on different people is about 93% (28 correct recognitions out of 30).